Innovating Islamic History Education: Implementing the Inquiry-Transactional Learning Model to Enhance Learning Quality in Vocational Schools - Khoirawati, Khoirawati; Yaqin, Lalu Nurul; Yamkee, Abduhakim Kajee (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
The teaching of Islamic history in Vocational High Schools still predominantly relies on conventional lecture methods, which often result in low student engagement and comprehension. This study aims to develop and assess the effectiveness of the Inquiry-Transactional Learning Model in improving students' understanding of Islamic history. Applying a Research and Development (R&D) approach based on the Borg & Gall model, the study utilized observations, interviews, questionnaires, and pre-test and post-test evaluations. Data were analyzed using a paired sample t-test and qualitative analysis techniques. The results showed a significant improvement in students' understanding, as indicated by higher post-test scores compared to pre-test scores. Additionally, students demonstrated increased engagement, critical thinking, and motivation in learning Islamic history. The Inquiry-Transactional Learning Model has proven to be an effective and innovative approach in vocational school education, promoting active exploration and student-teacher interaction. Future research could focus on integrating this model with digital media to further enhance learning outcomes.